Childhood maltreatment, borderline personality features, and coping as predictors of intimate partner violence: $hAnnegret Krause-Utz, Lea J. Mertens, Julian B. Renn, Pauline Lucke, Antonia Z. Wöhlke, Charlotte C. van Schie, and Joanne Mouthaan - Krause-Utz, Annegret; Mertens, Lea Julia; Renn, Julian B.; Lucke, Pauline; Wöhlke, Antonia Z.; Schie, Charlotte C. van; Mouthaan, Joanne (Journal of interpersonal violence, 2021)
Intimate partner violence (IPV) is a serious mental and physical health concern worldwide. Although previous research suggests that childhood maltreatment increases the risk for IPV, the underlying psychological mechanisms of this relationship are not yet entirely understood.